Delay in Hospital Arrival of Stroke Patients: An Observational Study - Ahasan, H A M Nazmul; Kumar Sarkar, Prodip; Das, Aparna; Ayaz, KFM; Dey, Pritam; Ahmed Siddique, Ashfaque; Chowdhury, Mostofa Kamal; Hossain, Md. Yeanur; Minnat, Baharul; A.S. Hussain, Deena (Journal of Medicine, 2014)
Abstract: Introduction: Stroke is the leading cause of disability among adults globally. The importance of early intervention is well known to prevent permanent disability and mortality otherwise caused by the ischemic stroke or hemorrhagic stroke. Objective: Aims of this study are to assess the level of pre-hospital delay and reasons for such delay in acute stroke patients. Methods and Materials: An observational study was carried out in the Department of Medicine, Dhaka Medical College Hospital between December 2012 to January 2013 among stroke patients (Age greater than 18 years, both gender, with Clinical features and neuroimaging findings consistent with stroke). The questionnaire regarding patients age, sex, occupation, presenting symptoms, associated disease like DM, HTN etc., duration of symptoms, mode of transportation, type of consultation sought, causes of delay, their socio-economic status were filled up by investigator. Result: In our study out of 100 patients 55 (55%) had ischaemic stroke and 45 (45%) had haemorrhagic stroke. The median delay from onset of symptoms to hospital arrival was 6 hours. The main cause of delay in reaching hospital was identified as indecision (40%). The other causes include financial constrain (30%), non-availability of transport (22%), traffic jam (10%), lack of manpower (20%) and consultation with rural medical practitioners (30%). Conclusion: Early intervention is very important to prevent permanent disability and mortality in case of stroke. So, it is important to take necessary steps to raise awareness among health care professionals and general population reagarding handling stroke patients and sending them to specialized hospitals where adequate facilities are present. DOI: http://dx.doi.org/10.3329/jom.v14i2.18459 J Medicine 2013, 14(2): 106-109